Formation of productive and creative competence of future engineers-teachers under the conditions of an integrated creative-developmental educational space - Masych, V. (Problems of Engineer-Pedagogical Education, 2019)
The article is devoted to the problem of the formation of productive and creative competence of future engineers-teachers under the conditions of an integrated creative-developmental educational space. Educational space is defined as a system that includes the areas of development, upbringing and training; dynamic unity of subjects of the educational process and their relations. It is emphasized that the educational space, which combines social, upbringing and educational components, as well as the external and internal environment of each subject of the educational process, is characterized by saturation of the educational process with the spirit of knowledge, cooperation and co-creation. The atmosphere of students’ cooperation activates the mechanisms of intellectual development – the need-motivational setting and the creative activity of the learner. The article points out that in order to create an integrated creativedevelopmental educational space in a separate educational institution of a certain educational system, it is necessary to transform the factors of the creative-developmental educational environment of the sociopsychological orientation into a spiritually rich atmosphere of trust and creativity through the implementation of innovative ideas of pedagogy of cooperation.